Risk factors for disabilities among leprosy patients: A systematic review - Swati Chandrahas Kurane, Dr. Pravin Dani (South Eastern European Journal of Public Health, 2025)
Background:Physical disability is the main sequelae of leprosy disease that leads to stigma, discrimination, socioeconomic and healthcare burden. The countries with the highest number of new leprosy cases every year are India, Brazil, Indonesia, and Bangladesh. More than half of all new cases of leprosy in the world are diagnosed in India.Considering this, National Strategic Plan (NSP) and Roadmap for leprosy was launchedin January2023, for zero transmission of leprosy by 2027. However, newly reported leprosy cases still have high incidence of disabilities due to multiple factors. Methods and Materials: A total of 110 research articles were reviewed in the (PubMed, GoogleScholar, Cochrane library, Academia, Open access, Directory of open access journals) databasesby using the keywords “leprosy”, “disabilities”, risk factors”. Based on the inclusion and exclusion criteria studies were sorted out and 22 studies were selected for the main analysis. The present systematic review was conducted following published guidelines for reporting systematic reviews and meta-analysis (PRISMA). Results:Most studies used cross-sectional research design and significant studies were retrospective record based. Maximum studies were from India. Sample size ranged from 55 to 22585 cases. Age, male gender, duration of disease, delayed diagnosis, multibacillary lepromatous type of leprosy, number of affected nerves and leprosy reactions were among the most evaluated risk factors.